Empirical Testing of Business Process on Implementation of Accounting Information System - Rapina Rapina; Tan Ming Kuang; Dien Noviany Rahmatika; Fahmi Dwi Suhenda (Faculty of Economics and Business, University of Pancasakti Tegal, 2023)
Accounting is currently used in a variety of commercial processes. The commercial process relates to the information system used by the organization, where the implementation of the accounting information system when preparing the organization's financial reports is still experiencing some problems. The purpose of this study is to conduct empirical testing that business processes can have a significant effect on the use of accounting information systems for competitive advantage. The context of this study is that the implementation of accounting information systems in Indonesia based on the accounting data they produce is not satisfactory. The results of the research show that the accounting information system used is influenced by business processes. Implementation of accounting information systems has not been qualified in accordance with the expectations of the banking world. This is because the dimensions of business processes namely time, quality of internal processes, and process flexibility have not been fully considered in accounting information system implementation.